Hygiene sanitation aspect and drinking water quality of Kerawang Depots, Lampung - Winanti, Ganis Ayu; Sarto; Wiranto (Universitas Gadjah Mada, 2022)
Purpose: Healthy and safe refillable drinking water must comply with Permenkes RI No 43 Tahun 2014 and Permenkes RI No 492/MENKES/Per/IV/2010. Increasing drinking water coverage in Lampung Province makes Kerawang water an alternative to meet drinking water needs because it is cheap, easy to access, and practical. This study aims to analyze the hygiene and sanitation of the Kerawang water depot. Methods: This qualitative study used a case study approach. Informants were recruited through the purposive sampling technique. The primary informants are 6, the touchers of the depots. One supporting informant was the Ambarawa Health Center’s environmental health officer. Results: Of the 17 depots observed, 3 (17.64%) water depots did not meet the requirements, and 14 (82.35%) met the criteria. Of the 17 depots that had been checked the quality, 17 (100%) depots were appropriate for the physical requirements, 11 (64,70%) depots were not suitable for the chemical requirements, 2 depots (11.76%) were not appropriate for the biological requirements. Conclusion: The infrastructures were cleaned at different times, and there was some lack of basic sanitation facilities. Equipment for the water treatment process was always replaced before the expiration. Some handlers did not check their health and apply hygiene behaviors. Depot owners must complete basic sanitation facilities such as handwashing stations, trash cans, and closed sewers, facilitate work clothes and health checks, control the hygiene behaviors of handlers, and conduct regular quality checks on drinking water.